(untitled) (Research, Society and Development, 2020)
Objective: Identify the causes of decompensation and trends in the classification and treatment of hospitalized patients with heart failure. Methods: Observational study, carried out in a private cardiology reference hospital in the city of Aracaju / SE. Medical records from June 2015 to August 2018 were analyzed and questionnaires were applied to patients over 18 years old, who presented with acute form or acute exacerbation of chronic Heart Failure. Results: 180 patients were included, with a mean of 73 years and a male prevalence (52.2%). It was identified that 94.4% of the patients had dyspnea, 86.1% had a history of systemic arterial hypertension, arrhythmia (33.3%) was the main cause of decompensation and the hypertensive etiology was recognized in 39.4% of the cases. Heart Failure with reduced ejection fraction was identified in 50.7%, with a greater tendency in males (p<0.0001) and in younger people (p=0.001). Diuretics (82.3%) and beta-blockers (58.3%) were the main medications used chronically and during hospitalization 83.9% used loop diuretics for symptomatic improvement. The average hospital stay was 12.45 days and of the 6.1% who died, 72.7% required intensive care. Conclusion: The characteristics identified in patients with Heart Failure such as the association of several comorbidities and the growing diagnosis of patients with preserved ejection fraction demonstrate the need for new strategies to face this syndrome.